Comparison of Dmft and Oral Health Behavior of 7-9-Year-Old Iranian and Afghan Children - Rahimi Jafari, Mohammad; Faezi, Mojgan; Sajedi, Seyed Masoud (Galen Medical Journal, 2024)
Background: This study aimed to compare the dmft and oral health behavior of 7-9-year-old Iranian and Afghan children. Materials and Methods: This cross-sectional study was conducted on 87 Iranian and 70 Afghan children between 7-9 years, who were selected among elementary schoolchildren in Pishva, Iran by convenience sampling in 2023. The children underwent clinical dental examination by a dental explorer and a dental mirror under a head light to record their decayed, missed and filled teeth (dmft) index. Their oral health behavior was also evaluated by using a questionnaire completed by parents. Data were analyzed by the Chi-square test and Fisher’s exact test (alpha=0.05). Results: The dmft of Iranian children was significantly lower than of Afghan children (P<0.05). Also, Afghan children’s Oral health behavior. was lower than Iranian children (P<0.05) There was no significant difference between source of oral health information and toothbrushing technique between the two ethnic groups (P>0.05). Conclusion: Iranian 7-9-year-old children had lower dmft and superior oral health behavior than Afghan children, which highlights the effect of immigration and social and cultural factors on oral health behavior. Information drawn from this study can be helpful to design specific dental programms in order to provide better oral health for Afghan children.